Integrating Islamic Values and Place Identity to Enhance Halal Tourist Attractions among Tourists in Sumatra - Teuku Muhammad Syahrizal; Najla; Syahriyal; Cut Salwa Syarafina (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This study examines the influence of Islamic values on domestic tourists’ intention to visit Aceh, with place identity as a potential moderating variable. Aceh’s strong Islamic character positions it as an attractive destination for Muslim tourists from Sumatra. Employing a quantitative approach, data were collected from 119 respondents via questionnaire and analyzed using simple linear regression and Moderated Regression Analysis (MRA). Findings reveal that Islamic values have a significant positive effect on visit intention. Place identity also positively influences visit intention, but does not moderate the relationship between Islamic values and visit intention. These results indicate that Islamic values serve as a primary motivator for domestic tourists, while place identity exerts an independent effect on visit intention. Keywords: Islamic values, visiting interest, place identity, halal tourism, Aceh